(untitled) (Journal of Hama University, 2019)
This research aimed to evaluate the effectiveness of using linear programming in maximizing the profits of small and medium enterprises. And to achieve this objective, the linear programming method was used to plan the profits of one of medium enterprises operating in the Syrian Arab Republic for the period 2015-2017 by formulating a written programming model for the project and solving it using the solver function in Microsoft Office Excel and planning its revenues and costs based on the proposed solution, and then calculate the profitability ratios after the planning of profits using linear programming, and compare them before the planning process. The research was based on the analytical descriptive approach, where a number of hypotheses were developed and tested using the Mann-Whitney test within the statistical program SPSS. One of the most important results was that using the linear programming method in small and medium enterprises profit planning contributes to maximizing it, which has contributed to maximizing the gross profit margin, operating profit margin, and net profit margin of the project case study, and The absence of planning in its various forms (administrative, financial, production, marketing ...) is the main cause of most of the problems experienced by SMES. The absence of administrative planning leads to conflicting decisions and ends in failure. Leading to the waste of limited resources and loss of the project, the absence of financial planning and the irregularity of financial and accounting records is an obstacle to access to SMES on their financing needs of banks and financial institutions